2023
DOI: 10.3390/polym15132895
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Rigid Foams from Pineapple Field Waste

Abstract: Pineapple materials sourced from agricultural waste have been employed to process novel bio-degradable rigid composite foams. The matrix for the foam consisted of starch extracted from pineapple stem, known for its high amylose content, while the filler comprised non-fibrous cellulosic materials sourced from pineapple leaf. In contrast to traditional methods that involve preparing a batter, this study adopted a unique approach where the starch gel containing glycerol were first formed using a household microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Notably, a discernible decline in diffraction intensity ensued post-glycerol plasticization. This divergence stands in contrast to PSS films created through solution casting methods [ 34 , 35 ]. Additionally, an emerging peak around 18.6° is observed, likely linked to the V-type crystalline structure.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, a discernible decline in diffraction intensity ensued post-glycerol plasticization. This divergence stands in contrast to PSS films created through solution casting methods [ 34 , 35 ]. Additionally, an emerging peak around 18.6° is observed, likely linked to the V-type crystalline structure.…”
Section: Resultsmentioning
confidence: 87%
“…The water resistance of the starch-based materials was conducted in terms of the water absorption and solubility by following the procedure reported by Namphonsane et al [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound absorption coefficient was found above 0.5 for most of the bound and hybrid composites. New bio-degradable composite foams made of pineapple stem starch and pineapple leaves were reported by Namphonsane et al [23]. Their results indicated that the flexural strengths of the composite foams ranged from 1.5 to 4.5 MPa.…”
Section: Introductionmentioning
confidence: 93%